Unilateral Pulmonary Artery Aplasia in a Pregnant Patient. (7th April 2011) - Lal, Chitra; Barker, Jim; Strange, Charlie
Abstract : Unilateral pulmonary artery aplasia is a rare anomaly. Case reports of this condition in pregnant patients are even more uncommon and the best approach to management of such patients is still unclear. We report a patient who presented with a history of dyspnea, chest pain, and hemoptysis. Imaging established the diagnosis in a newly pregnant female. Management of the pulmonary artery aplasia patient in pregnancy requires prospective evaluation of pulmonary hypertension.